Interaction mechanism of rock with deep water - Rzayev Abbas Geydar Ogly; Rasulov Sakit Rauf Ogly (Федеральное государственное бюджетное образовательное учреждение высшего образования «Уральский государственный горный университет», 2018)
Relevance. Prediction of earthquakes is one of the most difficult actual problems of mankind. The complexity of the forecast is in the fact that, firstly, the processes in earthquake origin are stochastic and do not allow to give a deterministic evaluation. Secondly, the mechanism for generating the earthquake origin is not completely revealed. It is established that stress accumulation in the fault (at the boundaries of tectonic plates) is associated with the variation of local stress fields, the change in frictional coefficient in the fault, the variation in fluid processes, and so on. Consequently, the study of the mechanism of saturation of tiny fracture and the mechanism of rock interaction in the earthquake origin with juvenile water, which leads to earthquakes, is a very urgent task. Purpose of the work. Determination of the mechanism of rock interaction with deep water and the development of mathematical models of rock performance when subjected to loadings taking into account the nonlinear effect of the load diagram and rock fold diagram. Methodology of the study. The work gives the analysis of issues for determining the mechanism of earthquakes. A new approach to determination of this mechanism is proposed. It is shown that deep water is one of the determining factors in the beginning and development of earthquake origin. Results. A method for determining the mechanism of earthquakes beginning is proposed, as well as some mathematical models that approximate the experimental data of rock performance when subjected to loadings in the process of filtration of deep water into tiny fractures of rock in the earthquake origin taking into account the nonlinear effect. Conclusions. The current state of the earthquake prediction problem is analyzed. It is shown that the geodetic information for forecasting the location and strength of earthquakes is more accurate. The way of rock fragmentation under general compression is shown. The nature of stress accumulation in the earthquake origin is described. The mathematical models are proposed; they sufficiently (with an average relative error of 2.13%) describe the experimental data obtained while loading rock samples taking into account the mode of dilatancy
Keywords: ГОРНАЯ ПОРОДА; ВОДА; ЗЕМЛЕТРЯСЕНИЕ; ТРЕЩИНА; ТЕКТОНИЧЕСКОЕ СМЕШЕНИЕ; СЕЙСМОГЕННЫЙ РАЗЛОМ; ROCK; WATER; EARTHQUAKE; FRACTURE; TECTONIC MIXING; SEISMOGENIC FAULT; 551.24